#TITLE_ALTERNATIVE# - LINGGARSARI NIETIADI (NIM 102 03 008) ; pembimbing : Dr.rer.nat. Bobby Eka Gunara, MAUREEN
This final project explain how around non degenerate vacuum reacts and N=1 chiral supersymmetry which have KÃƒÂ¤hler metric, which its scalar potential does not have degenerate critical points, so Morse theory can be used in this analysis. The result expected in this final project is a general and specific solution of Klein Gordon scalar field with harmonic oscillator interaction. We derive Hamiltonian function of the solution.